The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0004-27492006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Use of amniotic membrane in trabeculectomy for the treatment of glaucoma: a pilot study

Abstract: Trabeculectomy with amniotic membrane and standard trabeculectomy promote lower postoperative intraocular pressure although results showed no statistically significant difference between groups regarding postoperative intraocular pressure after one year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Eighteen studies, reported in 17 full-text articles and one conference abstract, assessed the use of amniotic membrane compared with trabeculectomy, with or without the use of MMC (Bruno 2008;Cai 2012;Cho 2013;Eliezer 2006;Huang 2007;Ji 2013;Khairy 2015;Li 2010;Liu 2009;Ren 2009;Sheha 2008;Stavrakas 2012;Wang 2008;Wang 2009;Yan 2004;Yang 2004;Zhang 2009;Zheng 2005). Findings from 13 of these studies were published in Chinese and accounted for 647 eyes of 536 participants, more than 70% of all 726 participants in the 18 studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighteen studies, reported in 17 full-text articles and one conference abstract, assessed the use of amniotic membrane compared with trabeculectomy, with or without the use of MMC (Bruno 2008;Cai 2012;Cho 2013;Eliezer 2006;Huang 2007;Ji 2013;Khairy 2015;Li 2010;Liu 2009;Ren 2009;Sheha 2008;Stavrakas 2012;Wang 2008;Wang 2009;Yan 2004;Yang 2004;Zhang 2009;Zheng 2005). Findings from 13 of these studies were published in Chinese and accounted for 647 eyes of 536 participants, more than 70% of all 726 participants in the 18 studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Incomplete outcome data-Of the 33 studies, investigators of 17 studies reported few or no losses to follow-up, resulting in our assessment of them to be at low risk of attrition bias: four of six trials of Ex-PRESS (Dahan 2012;De Jong 2009;Netland 2014;Wagschal 2013), five of eight studies for Ologen (Cillino 2011;Marey 2013;Papaconstantinou 2010;Rosentreter 2010;Rosentreter 2014), six of 18 studies for amniotic membrane (Cai 2012;Eliezer 2006;Ji 2013;Khairy 2015;Liu 2009;Stavrakas 2012), one study for E-PTFE (Cillino 2008), and one study for Gelfilm (Birt 1998). Four studies had a relatively large percentage of losses to follow-up (> 10%) and we assessed the risk of attrition bias to be high for these studies (Bruno 2008;Cho 2013;Senthil 2013;Sheha 2008).…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations